Sistem Pendukung Keputusan Penilaian Kinerja Karyawan Pada PT Manggala Usaha Manunggal Menggunakan Metode Analytical Hierarchy Process (AHP) - Sella Marta Armelia; Firamon Sakti (Training & Research Institute - Jeramba Ilmu Sukses, 2021)
PT Manggala Usaha Manunggal is a company engaged in mining and focusing on coal minerals, which is supported by many employees who work professionally in their respective fields. In a company, an employee performance appraisal process is usually carried out to determine the best employees. In the current performance appraisal process, the company still uses a manual system, so it is still less effective and efficient in managing data. The problem faced is how to calculate the best employee performance appraisal, with a decision support system in calculating employee performance appraisal, one of which is by applying the AHP (Analytical Hierarchy Porcess) method which is expected to produce the best employee rankings. The system that will be created will be web-based using MYSQL.